Comprehensive Sex Steroid Profiling in Multiple Tissues Reveals Novel Insights in Sex Steroid Distribution in Male Mice - Colldén Hannah; Nilsson Maria E; Norlén Anna-Karin; Landin Andreas; Windahl Sara H; Wu Jianyao; Gustafsson Karin L; Poutanen Matti; Ryberg Henrik; Vandenput Liesbeth; Ohlsson Claes (ENDOCRINE SOC, 2022)
A comprehensive atlas of sex steroid distribution in multiple tissues is currently lacking, and how circulating and tissue sex steroid levels correlate remains unknown. Here, we adapted and validated a gas chromatography tandem mass spectrometry method for simultaneous measurement of testosterone (T), dihydrotestosterone (DHT), androstenedione, progesterone (Prog), estradiol, and estrone in mouse tissues. We then mapped the sex steroid pattern in 10 different endocrine, reproductive, and major body compartment tissues and serum of gonadal intact and orchiectomized (ORX) male mice. In gonadal intact males, high levels of DHT were observed in reproductive tissues, but also in white adipose tissue (WAT). A major part of the total body reservoir of androgens (T and DHT) and Prog was found in WAT. Serum levels of androgens and Prog were strongly correlated with corresponding levels in the brain while only modestly correlated with corresponding levels in WAT. After orchiectomy, the levels of the active androgens T and DHT decreased markedly while Prog levels in male reproductive tissues increased slightly. In ORX mice, Prog was by far the most abundant sex steroid, and, again, WAT constituted the major reservoir of Prog in the body. In conclusion, we present a comprehensive atlas of tissue and serum concentrations of sex hormones in male mice, revealing novel insights in sex steroid distribution. Brain sex steroid levels are well reflected by serum levels and WAT constitutes a large reservoir of sex steroids in male mice. In addition, Prog is the most abundant sex hormone in ORX mice.